Eimeria lokuma n. sp. (Apicomplexa: Eimeriidae), a new coccidium from the African helmeted turtle Pelomedusa subrufa (Lacépède) (Testudines: Pelomedusidae) - Siroký, Pavel; Kamler, Martin; Modrý, David (Systematic parasitology, 2006)
Coprological examination of nine African helmeted turtles Pelomedusa subrufa from Kenya revealed the presence of a new coccidium belonging to Eimeria Schneider, 1875. Oöcysts of Eimeria lokuma n. sp. are spherical to sub-spherical, 13.6 (13-14.5) x 13 (12-14) microm, lack a micropyle and a polar granule, but possess a granular oöcyst residuum. The sporocysts are elongate, oval to spindle-shaped and 8.3 (7.5-9.5) x 4.4 (4-5) microm. The Stieda body is relatively low, flat and wide, and covered with a membranous, highly flexible, scarf-like structure which protrudes from its strengthened margins. The sporozoites possess two refractile bodies. Based on the presence of a Stieda body, the described species is classified as Eimeria (sensu stricto).
Keywords: Animals; želvy; Eimeria; Turtles; zvířata; feces; Feces